2000
DOI: 10.1007/bf02237428
|View full text |Cite
|
Sign up to set email alerts
|

Does technique of anastomosis play any role in developing late perianal abscess or fistula?

Abstract: The most important risk factor in developing perianal sepsis in long-term patients with ileal pouch-anal anastomosis is the initial disease type. After excluding patients without Crohn's disease, the risk of developing an abscess or fistula was found to be significantly greater in patients with chronic ulcerative colitis compared with patients with familial adenomatous polyposis, and this risk is independent of anastomotic technique.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
3
4

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 11 publications
1
27
3
4
Order By: Relevance
“…Although some authors showed favorable results toward stapled IPAA,5, 9, 12 others reported no benefit or a trend toward higher complications 13, 14. In the present study, the analysis revealed no significant difference in the rates of overall complications or extra‐pelvic complications between stapled and hand‐sewn IPAA.…”
Section: Discussioncontrasting
confidence: 53%
See 2 more Smart Citations
“…Although some authors showed favorable results toward stapled IPAA,5, 9, 12 others reported no benefit or a trend toward higher complications 13, 14. In the present study, the analysis revealed no significant difference in the rates of overall complications or extra‐pelvic complications between stapled and hand‐sewn IPAA.…”
Section: Discussioncontrasting
confidence: 53%
“…Some studies found higher incidence of septic complications, fistula and anastomotic stricture after hand‐sewn IPAA,5, 9, 12 whereas other studies showed a trend toward higher incidence of overall complications and stricture after stapled IPAA 13, 14. Importantly, most of the previous studies included patients with ulcerative colitis (UC) rather than patients with FAP 5, 8, 14, 15 although the complication rates were different between such patients 5, 8, 14, 15.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A presença de fístula, que pode ser vaginal, perianal ou perineal, está mais relacionada à doença de base do que à própria técnica cirúrgica utilizada (10) , ou seja, os doentes com PAF têm baixo risco para esta complicação, quando comparados aos doentes com doença inflamatória intestinal, submetidos a cirurgia do reservatório ileal (31,33,40) . Da mesma maneira, apesar da sepse pélvica estar mais relacionada aos doentes com doença inflamatória intestinal, esta complicação é causa importante de morbidade no pós-operatório da cirurgia do RI na PAF.…”
Section: -Abr/jun 2008unclassified
“…The prevalence of perianal fistulae varies between 3.6 and 12.7% [23,24,25]. Patients with a diagnosis of chronic UC have a significantly higher risk of developing perianal sepsis during in the long term following IPAA compared with those with familial adenomatous polyposis [26]. Although it is difficult to determine if perianal sepsis after IPAA arises from anastomotic dehiscence or the anal gland, except for patients who are clearly diagnosed with cuff abscess, these complications may cause pouch failures regardless of their origins [27].…”
Section: Discussionmentioning
confidence: 99%